THE QUESTIONS OF THE RATIONAL EFFICIENT USE RESURSNOGO POTENTIAL IN CONTEXT OF THE IMPROVEMENT TO TERRITORIAL ORGANIZATION PRODUCTION (ON EXAMPLE SOUTH ARAL REGION) - Umarova A. E. (Academia Science Repository, 2023)
In article is considered questions of the complex use natural-economic potential in context improvement to territorial organization of the branches production in administrative region lower reached Amudarii in order to increase in market conditions.